2018
DOI: 10.17244/eku.334590
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Relationship between Individual Innovative Levels and Individual Creatives of Science Teacher Candidates

Abstract: Öz Makale Bilgisi Bu çalışmanın amacı fen bilgisi öğretmen adaylarının bireysel yenilikçilik ve bireysel yaratıcılık düzeylerini belirlemek ve bireysel yenilikçilik düzeyleri ile bireysel yaratıcılıkları arasındaki ilişkiyi tespit etmektir. İlişkisel tarama modelinin kullanıldığı araştırma, 159 fen bilgisi öğretmen adayının katılımıyla gerçekleştirilmiştir. Araştırmada, Hurt, Joseph ve Cook (1977) tarafından geliştirilen; Kılıçer ve Odabaşı (2010) tarafından Türkçe 'ye uyarlanan "Bireysel Yenilikçilik Ölçeği" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
10
0
5
Order By: Relevance
“…The pre-service teachers' creative thinking tendencies were found to be above the medium. Yenice and Yavasoglu (2018) found the creative thinking tendencies as medium. Aydogdu and Yuksel (2013); Yildiz (2018) also found that the pre-service teachers' level of creative thinking is above the medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-service teachers' creative thinking tendencies were found to be above the medium. Yenice and Yavasoglu (2018) found the creative thinking tendencies as medium. Aydogdu and Yuksel (2013); Yildiz (2018) also found that the pre-service teachers' level of creative thinking is above the medium.…”
Section: Discussionmentioning
confidence: 99%
“…When the national literature is reviewed, it is seen that there are studies investigation pre-service teachers' entrepreneurship skills (Arpaci, 2015;Armut & Kilinc, 2018;Aydin & Oner, 2016;Celik, 2014;Deveci & Cepni, 2015b;Deveci & Cepni, 2017;Karademir, Balbag & Cemrek, 2018;Konokman & Yelken, 2014;Kostekci, 2016;Memduhoglu & Sahin, 2017;Ocak & Su, 2016;Pan & Akay, 2015;Senel & Kocaalan, 2018) creative thinking skills (Bakir & Oztekin, 2014;Cenberci & Yavuz, 2018;Cenberci, 2018;Demir Kacan, 2015;Gok & Erdogan, 2011;Gulel, 2006;Isleyen & Kucuk, 2013;Toyran, 2015;Topoglu, 2015;Yenice & Yavasoglu, 2018;Yildiz, 2018). However, there is no research examining the pre-service teachers' perceptions of entrepreneurship and creative thinking tendencies in relation to some variables and looking at the degree of the relationship between these two sets of skills.…”
Section: Creative Thinkingmentioning
confidence: 99%
“…Alanyazın incelendiğinde Türkiye'de yapılan çalışmaların çoğunda bireylerin yenilikçilik kategorilerinden "Sorgulayıcı" (Aslan ve Kesik, 2018;Çetin ve Bülbül, 2017;Çuhadar, Bülbül ve Ilgaz, 2013;Özgür, 2013) oldukları; bazı çalışmalarda ise "Öncü" (Akgün, 2017;Atçı, Kale ve Şeker, 2017;Yapıcı, 2016;Yılmaz ve Bayraktar, 2014) oldukları görülmüştür. Bireysel yenilikçilik düzeyinin cinsiyete göre farklılaşmadığını ortaya koyan çalışmalar (Akgün, 2017;Aslan ve Kesik, 2018;Çuhadar vd., 2013;Demir Başaran ve Keleş, 2015;Kert ve Tekdal, 2012;Korucu ve Olpak, 2015;Rogers, 2003;Rogers ve Wallace, 2011;Özgür, 2013;Yenice ve Yavaşoğlu, 2018) olduğu gibi, bireysel yenilikçilik düzeyinin cinsiyete göre farklılaştığını bulan (Demirsoy, 2005;Ertuğ ve Kaya, 2017;Gür-Erdoğan ve Zafer-Güneş, 2013;McQuiggan, 2006;Shim ve Kotsiopulos, 1994;Turhan, 2009) araştırmalar da vardır. Bireysel yenilikçilik düzeyinin çalışma alanına göre farklılaşmadığı bulguları (Adıgüzel, Kaya, Balay ve Göçen, 2014;Kılıç ve Ayvaz Tuncel, 2014;Örün, Orhan, Dönmez ve Kurt, 2015) (Arrosagaray vd., 2019;Hart, Chaparro ve Halcomb, 2008;Siddique, 2012;Wagner, Hassanein ve Head, 2010) gibi bazı özelliklerine göre farklılaşabilmektedir.…”
Section: Bireysel Yenilikçilikunclassified
“…Bulgulara göre erkek öğretmenlerin bireysel yenilikçilik özelliklerinin kadın öğretmenlerden daha yüksek bulunmuştur. Alanyazında bazı çalışmalarda erkeklerin kadınlardan daha yenilikçi (Demirsoy, 2005;Shim ve Kotsiopulos, 1994;Turhan, 2009), bazı çalışmalarda kadınların erkeklerden daha yenilikçi (Ertuğ ve Kaya, 2017;Gür-Erdoğan ve Zafer-Güneş, 2013;McQuiggan, 2006), bazı çalışmalarda ise yenilikçi olmanın cinsiyete göre farklılaşmadığı (Akgün, 2017;Aslan ve Kesik, 2018;Çuhadar vd., 2013;Demir Başaran ve Keleş, 2015;Kert ve Tekdal, 2012;Korucu ve Olpak, 2015;Özgür, 2013;Rogers, 2003;Rogers ve Wallace, 2011;Yenice ve Yavaşoğlu, 2018) bulguları görülmektedir. Bulguların birbirlerinden farklı çıkmasının nedeninin örneklemlerin özelliklerinden kaynaklandığı söylenebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation